A comprehensive review on bovine tropical theileriosis under Indian scenario - Singla, Lachhman Das; Kaur, Paramjit (Indian Journal of Veterinary Medicine, 2024)
Vector borne haemoprotozoan diseases are responsible for remarkable production losses due to mortality, the costs of treatment and the decrease in milk yield and average weight gain in animals especially in the cross bred and exotic cattle in the tropical and subtropical regions of the globe. Theileriosis is a group of tickborne diseases caused by protozoan parasites of the Theileria genus adversely affecting the livestock industry, but in bovines the two economically important pathogenic species are Theileria annulata and T. parva which are responsible for bovine tropical theileriosis and East Coast fever, respectively. The endemic distribution for T. annulata and T. parva is comparatively restricted. In India, T. parva has not been reported due to the absence of vector tick Rhipicephalus appendiculatus, however abundance data is available on the T. annulata transmitted by Hyalomma anatolicum ticks. It is a serious constraint to Indian dairy industry with more fatal infections in exotic cattle and substantial losses to cross-bred and indigenous zebu cattle. The clinical course of the bovine tropical theileriosis varies from subclinical to acute or per acute form. Disease is characterized by high fever, enlarged lymph nodes, weakness, weight loss, inappropriate appetite, conjunctival petechiation, and anaemia. The pathological changes attributed to cytokine production by Tlymphocyte proliferation resulting into pathognomonic lesions in the form of punched out necrotic ulcers. The intrinsic factors associated with epidemiology of T. annulata infection are species of animal, age, breed and sex. The decreared levels of haematological parameters viz. red blood cell (RBC) count, packed cell volume (PCV), haemoglobin (Hb) concentration are indicator of anaemia. The biochemical alterations provide a supportive diagnostic aid in the clinical cases. Molecular tools are a better option for diagnosis of the disease than the conventional and serological techniques. Among several control methods the most practical and widely used method is treatment with buparavaquone and the chemical control of ticks with acaricides. A sustainable approach for controlling Theileria infection in developing world is focused on integrated measures comprising of chemotherapy, vaccination and vector management